Genotoxicity - A Predictable Risk to Our Actual World 2018
DOI: 10.5772/intechopen.77968
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Risk in Human Populations Exposed to Pesticides

Abstract: The importance of early detection of genetic damage is that it allows taking the necessary measures to reduce or suppress the exposure to the deleterious agent when it is still reversible, thus decreasing the risk of developing diseases. For this reason, genotoxicity tests should be considered as indispensable tools in the implementation of a complete medical surveillance in people potentially exposed to various environmental pollutants and especially those who live in the same place with people who have alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In this context, agricultural workers and their families and individuals who reside close to fields where pesticides are applied are considered to be the group that will receive the most considerable exposure at the highest risk for adverse health outcomes ( Gangemi et al, 2016 ; Docea et al, 2017 ; Jacobsen-Pereira et al, 2018 ; Godoy et al, 2019 ; Marcelino et al, 2019 ). As a result, humans exposed to a complex mixture of pesticides are more likely to develop different diseases due to deleterious effects on immune, hematological, nervous, endocrine, and reproductive systems ( Corsini et al, 2013 ; Aroonvilairat et al, 2015 ; Campos et al, 2016 ; Corral et al, 2017 ; Docea et al, 2017 ; Koh et al, 2017 ; Aiassa, 2018 ; Jacobsen-Pereira et al, 2018 ; Godoy et al, 2019 ; Paumgartten, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, agricultural workers and their families and individuals who reside close to fields where pesticides are applied are considered to be the group that will receive the most considerable exposure at the highest risk for adverse health outcomes ( Gangemi et al, 2016 ; Docea et al, 2017 ; Jacobsen-Pereira et al, 2018 ; Godoy et al, 2019 ; Marcelino et al, 2019 ). As a result, humans exposed to a complex mixture of pesticides are more likely to develop different diseases due to deleterious effects on immune, hematological, nervous, endocrine, and reproductive systems ( Corsini et al, 2013 ; Aroonvilairat et al, 2015 ; Campos et al, 2016 ; Corral et al, 2017 ; Docea et al, 2017 ; Koh et al, 2017 ; Aiassa, 2018 ; Jacobsen-Pereira et al, 2018 ; Godoy et al, 2019 ; Paumgartten, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various in vitro and in vivo studies, as well as epidemiological approaches, have demonstrated that pesticides or their metabolites may result in genotoxic and mutagenic effects ( Bolognesi, 2003 ; Docea et al, 2017 ; Kapeleka et al, 2019 ; Paumgartten, 2020 ). Therefore, the use of genotoxicity and mutagenicity biomarkers is relevant to provide early identification of biological effects ( Kapka-Skrzypczak et al, 2011 ; Aiassa, 2018 ; Lozano-Paniagua et al, 2018 ). For assessment of mutagenic and genotoxic pesticide-induced damage, the most widely used methods are sister chromatid exchange assay, chromosomal aberrations test, single-cell gel electrophoresis (comet) assay, and micronuclei test ( Aiassa, 2018 ; Godoy et al, 2019 ; Kapeleka et al, 2019 ; Marcelino et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic activities disseminate large amounts of chemical substances into the environment [ 1 ]. Hence, humans are currently exposed to several pollutants with genotoxic potentials such as metals [ 2 ], pesticides [ 3 ], industrial waste mix [ 4 ], and nanomaterials [ 5 ]. Genotoxicity is a wide term comprising DNA damage and mutagenicity, where the mutagenic effect is described as an occurred event with irreversible and heritable outcomes affecting the DNA and/or chromosome structure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of clinical and experimental studies have taken place around the globe suggesting that diverse chemicals and mutagens can produce genotoxic effects in multiple tissues and cells. 1,2 Genotoxicity denotes, in genetics, a destructive effect(s) on a cell's genetic material (i.e., DNA, RNA), thus potentially altering cell integrity functions, and phenotypes.…”
Section: Introductionmentioning
confidence: 99%